1964
DOI: 10.1182/blood.v23.2.146.146
|View full text |Cite
|
Sign up to set email alerts
|

Protein Metabolism and Erythropoiesis. II. Erythropoietin Formation and Erythroid Responsiveness in Protein-deprived Rats

Abstract: (1) Rats on a normal and non-protein diet were hypertransfused to suppress their endogenous erythropoietin formation. Injection of erythropoietin elicited nearly identical increases in radioiron incorporation in the two dietary groups. (2) Normal and protein-starved rats were exposed to lowered atmospheric pressure. At each level of hypoxia the erythropoietin titer in the plasma of protein-starved rats were significantly lower than those in normal diet groups. (3) Re-proteinizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Reissman (1964) reported anaemia in malnourished rats and suggested as a mechanism a slow-down in protein synthesis in erythroid cells and/or a reduction in erythropoietin synthesis. Aschkenasy (1957) observed, in protein malnutrition, the presence of anaemia and leucopenia, and erythroid marrow hyperplasia without a simultaneous elevation in erythropoietin concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reissman (1964) reported anaemia in malnourished rats and suggested as a mechanism a slow-down in protein synthesis in erythroid cells and/or a reduction in erythropoietin synthesis. Aschkenasy (1957) observed, in protein malnutrition, the presence of anaemia and leucopenia, and erythroid marrow hyperplasia without a simultaneous elevation in erythropoietin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (Fried & Gurney, 1965; Seifter et al 1971; Aschkenasy, 1975) have demonstrated that, in rats, a fall in erythropoietin occurred due to the reduced ingestion of protein, in opposition to the results obtained in our study. Serum concentrations of erythropoietin were found to be both increased (Macdougall et al 1982; el-Nawawy et al 2002) and decreased (Reissman, 1964; Catchatourian et al 1980) in protein malnutrition and protein-energy malnutrition, the reduction being attributed to a decrease in the speed of O use by the tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] examined overall toxicological parameters with feed restriction for 2 weeks at 75, 50 or 25% of the control diet and found a myelosuppression in bone marrow in all the feed-restricted groups, indicating that the primary response to the feed restriction was hematopoietic suppression in rats. Other examinations focusing on hematopoiesis in feed-restricted rodents showed a decreased blood cell count and hypocellularity in bone marrow [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 15 , 17 , 19 ]. These rodent examinations suggested, as described by a number of review articles [ 15 , 21 , 22 ], the importance of hematopoietic evaluation in the malnourished condition.…”
Section: Introductionmentioning
confidence: 99%
“…From another perspective, individuals with elevated folate may be consuming foods high in folate, which are also high in phytates, ultimately reducing Fe absorption, a hypothesis that we could not test in this analysis. Further, those consuming high cereal diet, resulting in high folate, may also have lower intake of high-quality protein necessary for Hb production ( 58 ) .…”
Section: Discussionmentioning
confidence: 99%